2007
DOI: 10.1016/j.catena.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Runoff generation in a degraded Andean ecosystem: Interaction of vegetation cover and land use

Abstract: Tropical mountain regions are affected by rapid land use/-cover change, which may threaten their (eco-)hydrological functions. Although there is a growing interest in evaluating the effect of land use/-cover change on mountain hydrology, quantitative assessments of the impact of land use/-cover on hydrological processes are hampered by the lack of field measurements characterizing runoff generation processes. In this paper, we present results from field experiments of rainfall runoff mechanisms in the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 37 publications
4
109
0
5
Order By: Relevance
“…For instance land use and water areas have higher runoff coefficient due to their low infiltration rate; while the grass land, shrubs and forest areas have low runoff coefficient [36]. The rainfall runoff experiments indicate that degraded and abandoned land generate surface runoff within a few minutes after the start of the rainfall event [35,37]. One of the paper cited by [35] showed that runoff coefficient of natural vegetation and fallows area, cultivated land and barren land are 13%, 20% and 50% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For instance land use and water areas have higher runoff coefficient due to their low infiltration rate; while the grass land, shrubs and forest areas have low runoff coefficient [36]. The rainfall runoff experiments indicate that degraded and abandoned land generate surface runoff within a few minutes after the start of the rainfall event [35,37]. One of the paper cited by [35] showed that runoff coefficient of natural vegetation and fallows area, cultivated land and barren land are 13%, 20% and 50% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Forest conversion to more intensive forms of land use is often accompanied by soil compaction and degradation, which can reduce infiltration rates and increase rainfall-runoff responses (Molina et al 2007, Zimmermann and Elsenbeer 2009, Bathurst et al 2011, Ghimire et al 2013). At our Veracruz site, despite generally higher topsoil bulk density and much lower saturated hydraulic conductivity under pasture compared to regenerating and mature cloud forests (0.49 ± 0.06, 0.45 ± 0.11, and 0.25 ± 0.17 g cm -3 , and 30 ± 14, 615 ± 690, and 777 ± 931 mm h -1 , respectively) (Muñoz-Villers et al 2015), prevailing rainfall intensities at this elevation rarely exceeded topsoil infiltration capacities to generate flood-producing rates of overland flow (Muñoz-Villers and McDonnell 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that plant biomass and productivity increased significantly with increasing soil infiltration rates, which have close relationships with covered vegetation types (Benegas et al, 2014;Finley and Glenn, 2010;Fu et al, 2015;Zhang et al, 2014;Zheng et al, 2015). In addition to types and coverage degrees of vegetation (Cerdà, 1998;Molina et al, 2007), precipitation patterns , antecedent soil water content (Guo et al, 2014) and soil properties (Neris et al, 2012) also play the influential role in the water infiltration process.…”
Section: Introductionmentioning
confidence: 99%